Normal Mode Solutions of Target Strengths of Solid-filled Spherical Shells and Discussion of Influence Parameters - JIA, Bing; FAN, Jun; LI, Gui-Juan; WANG, Bin; CHEN, Yun-Fei (Archives of Acoustics, 2024)
The normal mode solution for the form function and target strength (TS) of a solid-filled spherical shell is derived. The calculation results of the spherical shell’s acoustic TS are in good agreement with the results of the finite element method (FEM). Based on these normal mode solutions, the influences of parameters such as the material, radius, and thickness of the inner and outer shells on the TS of a solid-filled spherical shell are analyzed. An underwater spherical shell scatterer is designed, which uses room temperature vulcanized (RTV) silicone rubber as a solid filling material and does not contain a suspension structure inside. The scatterer has a good TS enhancement effect.